2023
DOI: 10.3390/ph16070918
|View full text |Cite
|
Sign up to set email alerts
|

Indole-Acrylonitrile Derivatives as Potential Antitumor and Antimicrobial Agents—Synthesis, In Vitro and In Silico Studies

Abstract: A series of 2-(1H-indol-2-yl)-3-acrylonitrile derivatives, 2a–x, 3, 4a–b, 5a–d, 6a–b, and 7, were synthesized as potential antitumor and antimicrobial agents. The structures of the prepared compounds were evaluated based on elemental analysis, IR, 1H- and 13NMR, as well as MS spectra. X-ray crystal analysis of the representative 2-(1H-indol-2-yl)-3-acrylonitrile 2l showed that the acrylonitrile double bond was Z-configured. All compounds were screened at the National Cancer Institute (USA) for their activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…As a result, the trend of the RGyr plot versus simulation time and its low fluctuation surely explain the residual backbone and how folding of the EGFR protein remained stable after interaction with compounds 2f and 2g. [35][36][37][38][39][40][41] An in silico study (Table 4) of the most biologically active synthesized compounds 2f and 2g has been assessed by Swiss ADME server. Lipinski's rule states that both investigated molecules satisfied this rule and thereby should be taken orally.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the trend of the RGyr plot versus simulation time and its low fluctuation surely explain the residual backbone and how folding of the EGFR protein remained stable after interaction with compounds 2f and 2g. [35][36][37][38][39][40][41] An in silico study (Table 4) of the most biologically active synthesized compounds 2f and 2g has been assessed by Swiss ADME server. Lipinski's rule states that both investigated molecules satisfied this rule and thereby should be taken orally.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…Our findings revealed that 2f and 2g could be good templates for further drug discovery and development. [35][36][37][38][39][40][41] An in silico study (Table 4) of the most biologically active synthesized compounds 2f and 2g has been assessed by Swiss ADME server. Lipinski's rule states that both investigated molecules satisfied this rule and thereby should be taken orally.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…22–24 It is reported that nitrile group modified complexes show good antibacterial activity against Gram-positive and Gram-negative bacteria. 25–27 Importantly, the nitrile group can be used as bioactive “warheads” to hydrogen bond with proteins. 28 The nitrile group has significant effects on bacterial communities due to its conjugation effects.…”
Section: Introductionmentioning
confidence: 99%